Pengaruh Gerakan Literasi Sekolah (GLS) terhadap Minat Baca Siswa di Kelas Tinggi SDN 25 Singkawang - Nurramadiyanti Nurramadiyanti; Rini Setyowati; Abdullah Basith (FKIP, Universitas Palangka Raya, 2026)
The School Literacy Movement (GLS) is one of the government's steps in instilling and growing interest in reading. Interest in reading is a feeling of preference and interest in reading activities which is aimed at the desire and tendency to pay attention to this activity without anyone ordering it or doing it consciously. This research aims to determine whether or not there is an influence of the school literacy movement on students' reading interest in high grades and to determine the magnitude of the influence of the literacy movement on students' reading interest in high grades. This type of research is a quantitative approach and uses a causal associative research design. The sample in this study was all students in high grades IV, V and VI. The sampling technique in this research uses a saturated sampling technique with certain considerations. The data collection technique in this research is indirect communication and research instruments in the form of a school literacy movement questionnaire and a reading interest questionnaire. The data analysis technique used is simple linear regression. The results of this study show that: 1) The effect of GLS on reading interest is 0.020 (p > 0.05). 2) The magnitude of the influence of GLS on reading interest is 0.001 (0.1%). In conclusion 1) There is no influence between the school literacy movement on students' reading interest. 2) The influence of GLS on students' reading interest is in the very low category.